Genetic diversity and phylogenetic analysis of the ORF5 gene of PRRSV from central China. (December 2017) - Zhang, Liujun; Feng, Yan; Martin, Darren P.; Chen, Jing; Ma, Sixu; Xia, Pingan; Zhang, Gaiping
Abstract: To more fully understand the genetic diversity and molecular epidemiology of prevailing porcine reproductive and respiratory syndrome virus (PRRSV) in Henan province of China, 112 full-length ORF5 gene sequences, originating from Henan province between 2006 and 2015, were subjected to sequence variation and phylogenetic analysis. Phylogenetic analysis revealed that all Henan isolates belonged to the Type 2 genotype and could be further divided into three subgroups. Subgroup 1 and 2 viruses predominated in Henan and subgroup 2 overtook subgroup 1 as the most prevalent PRRSV between 2006 and 2015. Highly pathogenic PRRSV (HP-PRRSV) isolates predominated in Henan and eight RespPRRSV MLV vaccine-like isolates were observed in subgroup 3. Sequence variation analysis revealed that the ORF5 genes of all Henan isolates shared > 83.3% nucleotide and > 80.1% amino acid sequence identity with each other. Primary neutralizing epitope (PNE) analysis revealed that, relative to the attenuated RespPRRSV MLV vaccine isolate, all but one of the subgroup 1 Henan isolates had mutations at amino acid 39 within the key PNE of GP5. Analysis of the immunoreceptor tyrosine-based inhibitory motif (ITIM) in GP5 revealed that all but two of the Henan isolates had a highly conserved sequence between amino acids 77 and 82 positions of GP5. N-linked glycosylation site (NGS) analysis revealed a novel potential NGS at GP5 amino acid position 59 in two of the subgroup 2 Henan isolates. Another novel GP5 amino acid mutation ( 44 N →  44 D) was found in a single subgroup 1 Henan isolate (HeNan-A9) in a glycosylation site that is known to be crucial for PRRSV infectivity. Highlights: Henan isolates have undergone a shift from subgroup 1 to 2. The ORF5 gene of Henan isolates presented a high variation. Nearly all Henan isolates had a conserved ITIM at 77aa-82aa of GP5. A novel NGS at 59aa of GP5 was found in 2 Henan isolates. A novel mutation at N 44 glycosylation site of GP5 was found in HeNan-A9.